Fading shooting stars: The relative age effect, misallocation of talent, and returns to training in German elite youth soccer - Lukas Tohoff; Mario Mechtel (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2022)
This paper analyses the Relative Age Effect (RAE) in German elite youth soccer academies. We examine the efficiency of talent selection and the returns to training. Our results indicate a strong effect of players' birth dates on their probability of getting selected - and, thus, a waste of talent. Using data on 2,382 former elite youth players and their later market values, we find that clubs could generate 30.3 to 77.2% higher market values when eliminating the RAE. Our findings emphasize that distinguishing between current and potential performance levels is crucial for the efficient allocation of talent in sports and society.
Keywords: J24; Z22; M51; M53; I24; I26; D71; 330; Relative age effect; market values; misallocation of talent; returns to training; selection of talent; elite youth soccer